El arte de Zamora Vicente en el cuento Comida a la carta - Postigo Aldeamil, María Josefa (Revista de Filología Románica, 2008)
During the 70’s, Alonso Zamora Vicente († 14 March 2006) lecturer, philologist, member of the Spanish Language Academy and narrator wrote several short stories in which the essential features of his clear and unmistakable narrative style are succinctly shown. Taking the chosen text as a reference we will refer to the literary art: the content, the context and the linguistic elements.